ANALYSIS OF ADOLESCENT PROBLEM GAMBLING AND INTERVENTION MODES - Dorasamy, Jirushlan (International Journal of Psychosocial Rehabilitation, 2020)
Frequent gambling activities may include lotteries, sports betting, slot machines, blackjack, instant win games, online gambling, and scratch cards. As a behavioral disorder, problem or pathological gambling is characterized by preoccupation with the disorder, diminished control over gambling, and recurrent maladaptive behavior (Coyne et al., 2015). Rather than gambling being a leisurely pursuit, problem gamblers pursue it to alleviate their negative emotions and moods.